Odpowiedzi

Najlepsza Odpowiedź!
2009-11-12T19:36:27+01:00
A) 7( x² -3x -2)- 3(x²- 6x +1) dla x = -0,2
7( x² -3x -2)- 3(x²- 6x +1) = 7(0,04+0,6-2)-3(0,04+1,2+1) = 7*(-1,36)-3*2,24 =
-9,52-6,72= -16,24


b)x(3xy -y)- y(x²- xy +x) dla x= -1, y= ⅕
-1[(-⅗)-⅕] - (-1)[1-(-⅕)+(-1)] = ⅘ - (-1)[1⅕+(-1)] = ⅘-(-⅕) = ⅘+⅕ = 1
6 4 6
2009-11-12T20:07:03+01:00
A) 7( x² -3x -2)- 3(x²- 6x +1) dla x = -0,2
7( x² -3x -2)- 3(x²- 6x +1)=7((-0,2)²-6×(-0,2)+1)=
7(0,04-0,6-2)-3(0,04+12+1)=
7×(-2,56)-3×13,04=-17,92-39,12=-57,04




b)x(3xy -y)- y(x²- xy +x) dla x= -1, y= ⅕
x(3xy -y)- y(x²- xy +x)=-1(3×(-1)× ⅕+(-1)=
-1(-3× ⅕- ⅕)- ⅕(1+1× ⅕-1)=
-1(-1- ⅕)- ⅕× ⅕=1+ ⅕- ⅕× ⅕=1 ⅕-¹/₉=⁴/₃-¹/₉=¹²/⁹-¹/₉=¹¹/₉=1²/₉

5 2 5